Impacts of Warming on Reciprocal Subsidies Between Aquatic and Terrestrial Ecosystems - O’Gorman, Eoin J.; Chemshirova, Irina; McLaughlin, Órla B.; Stewart, Rebecca I. A. (Frontiers in Ecology and Evolution, 2021)
Cross-ecosystem subsidies are important as their recipients often rely on them to supplement in situ resource availability. Global warming has the potential to alter the quality and quantity of these subsidies, but our knowledge of these effects is currently limited. Here, we quantified the biomass and diversity of the invertebrates exchanged between freshwater streams and terrestrial grasslands in a natural warming experiment in Iceland. We sampled invertebrates emerging from the streams, those landing on the water surface, ground-dwelling invertebrates falling into the streams, and those drifting through the streams. Emerging invertebrate biomass or diversity did not change with increasing temperature, suggesting no effect of warming on aquatic subsidies to the terrestrial environment over the one-month duration of the study. The biomass and diversity of aerial invertebrates of terrestrial origin landing on the streams increased with temperature, underpinned by increasing abundance and species richness, indicating that the greater productivity of the warmer streams may attract more foraging insects. The biomass of ground-dwelling invertebrates falling into the streams also increased with temperature, underpinned by increasing body mass and species evenness, suggesting that soil warming leads to terrestrial communities dominated by larger, more mobile organisms, and thus more in-fall to the streams. The biomass and diversity of terrestrial invertebrates in the drift decreased with temperature, however, underpinned by decreasing abundance and species richness, reflecting upstream consumption due to the higher energetic demands of aquatic consumers in warmer environments. These results highlight the potential for asynchronous responses to warming for reciprocal subsidies between aquatic and terrestrial environments and the importance of further research on warming impacts at the interface of these interdependent ecosystems.